2001
DOI: 10.1021/jo005666q
|View full text |Cite
|
Sign up to set email alerts
|

Samarium(0) and 1,1‘-Dioctyl-4,4‘-Bipyridinium Dibromide:  A Novel Electron-Transfer System for the Chemoselective Reduction of Aromatic Nitro Groups

Abstract: A mild and efficient electron-transfer method was developed for the chemoselective reduction of aromatic nitro groups using samarium(0) metal in the presence of a catalytic amount of 1,1'-dioctyl-4,4'-bipyridinium dibromide. This method was found to give the product aromatic amine in 79-99% yield with selectivity over a number of other functional and protecting groups such as alkene, azide, benzyl ether, nitrile, amide, halide, p-toluenesulfonamide, t-Boc, tert-butyldiphenylsilyl ether, and aliphatic nitro gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
56
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(58 citation statements)
references
References 58 publications
0
56
2
Order By: Relevance
“…In addition, the reduction of aromatic nitro compounds often stops at an intermediate stage, yielding hydroxylamine, hydrazine, and azoarene products. [9] In this sense, there is a strong incentive to develop new simple, efficient, easily-handled procedures that can allow the highly chemo-and regioselective reduction of the nitro group under mild conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the reduction of aromatic nitro compounds often stops at an intermediate stage, yielding hydroxylamine, hydrazine, and azoarene products. [9] In this sense, there is a strong incentive to develop new simple, efficient, easily-handled procedures that can allow the highly chemo-and regioselective reduction of the nitro group under mild conditions.…”
mentioning
confidence: 99%
“…Many conventional procedures involving hydride reducing agents, hydrogenation, or indium failed to give such a high regioselectivity. [9,15] Recently, the regioselective reduction of [f]…”
mentioning
confidence: 99%
“…The Chloroand fluoro-substituted nitroarenes (Table 2, entries 3 and 4) were selectively reduced to the respective haloaromatic amines without any dehalogenation, which is often encountered with several procedures such as hydrogenation. [68][69][70][71] An analysis of the results of Table 2 shows that the best yields were obtained with substrates containing electron-withdrawing groups (entries 5-8). The ketone, carboxylic acid, and aldehyde functionalities present in the aromatic ring also remained unaffected during reduction of the corresponding nitrobenzenes by this procedure (entries 5-8).…”
Section: Resultsmentioning
confidence: 99%
“…Formation of such intermediates is oen observed with many other reducing agents. 16,30 When nitrosobenzene or phenylhydroxylamine was treated with Ag-RANEY® nickel and NaBH 4 in aqueous solution at 35 C, the nal product was aniline and it can be concluded that the following reaction path rationalized the overall reduction.…”
Section: 28mentioning
confidence: 99%